Insidious. The last key [videorecording (DVD)] - Whannell, Leigh, 1977-; Whannell, Leigh, 1977-; Shaye, Lin, 1944-; Sampson, Angus (Sony Pictures Home Entertainment, 2018)
Parapsychologist Dr. Elise Rainier faces her most fearsome and personal haunting yet; in her own family home.